Pembelajaran PAI berbasis Multiple Intelligences : Studi di SDIT BIAS Giwangan, Yogyakarta - Husna, Difa'ul; Pamungkas, Oktri (LP2M STAI Darul Kamal NW Kembang Kerang, 2024)
Each child is born with different intelligence potential, so ideally the learning process can be held by respecting each type of student intelligence according to his nature. This study aims to determine the learning implementation applied to the learning of Islamic Religious education based on multiple intelligences at SDIT BIAS Giwangan. The researcher used a descriptive qualitative method to describe the data obtained using interview, observation, and documentation techniques. The validity of the data is checked by data triangulation. Furthermore, data analysis is carried out by data reduction, presentation, and conclusion drawing. The results of the study show that: 1) Learning planning is carried out with Multiple Intelligences Research and the preparation of a syllabus and RPP; 2) The implementation of learning is carried out in preliminary activities, core activities, and closing activities; 3) Learning evaluation is carried out by paying attention to the cognitive, affective, and psychomotor domains.